Effect of mandatory sustainability performance disclosures on firm value: Evidence from listed European firms - Madhavan Vishnu Nampoothiri; Oliver Entrop; Thillai Rajan Annamalai (Corporate Social Responsibility and Environmental Management, 2024)
Corporate Sustainability Performance (CSP) reporting is becoming increasingly important to investors who seek to identify and invest in companies that are managing their Environmental, Social and Governance (ESG) risks effectively. The European Union's Non-Financial Reporting Directive (NFRD), which was implemented in 2017, mandates that certain large companies must disclose their sustainability performance. This study examines the impact of the EU NFRD on the firm value of listed European firms using a difference-in-differences regression model. We find that the mandatory disclosure of corporate sustainability performance does not significantly affect firm value at an aggregate level. However, the results suggest minor inter-industry differences, which can be attributed to varying sustainability performance metrics across industries. These findings contribute not only to the nascent literature on mandatory sustainability disclosures but also to the deliberations of policymakers and regulators across the world who are devising and implementing mandatory corporate sustainability performance disclosure regulations.
Keywords: 650; corporate social responsibility; ESG; firm value; mandatory disclosure; non-financial reporting; sustainability